Handbook of medicinal herbs - A Duke, James (CRC, 2012)
Still considered the definitive work on medicinal herbs and their uses after two decades, the Handbook of Medicinal Herbs has undergone a long-anticipated revision. In this second edition, world-renowned ethnobotanist James A. Duke provides up-to-date information on over 800 of the world's most important medicinal plant species. The book contains more species, phytochemicals, proven indications, folk indications, and dosage data than the first edition in a new, easier to use format. The in-depth content and the addition of color plates and over 200 black and white illustrations make this book the complete resource on medicinal herbs. Blending scientific fact with folk uses and the author's personal experience, Handbook of Medicinal Herbs, Second Edition provides the most well rounded discussion of safety, efficacy, toxicity, and rational use of medicinal herbs available." "See what's new in the second edition: over 100 color plates, 4 color maps; over 200 black and white illustrations; over 800 medicinal plants organized alphabetically by common name; more herbs from the African, Ayurvedic, Chinese, and Jamu traditions.